Free will, agency, and selfhood in Indian philosophy - Dasti, Matthew R.; Bryant, Edwin F. (Edwin Francis), 1957- (Oxford, Oxford University Press, 2014)
"Led by Buddhists and the yoga traditions of Hinduism and Jainism, Indian thinkers have long engaged in a rigorous analysis and reconceptualization of our common notion of self. Less understood is the way in which such theories of self intersect with issues involving agency and free will; yet such intersections are profoundly important, as all major schools of Indian thought recognize that moral goodness and religious fulfillment depend on the proper understanding of personal agency. Moreover, their individual conceptions of agency and freedom are typically nodes by which an entire school's epistemological, ethical, and metaphysical perspectives come together as a systematic whole. This book explores the contours of this issue, from the perspectives of the major schools of Indian thought. With new essays by leading specialists in each field, this volume provides rigorous analysis of the network of issues surrounding agency and freedom as developed within Indian thought." -- Back cover
Agency in Samkhya and Yoga / Edwin F. Bryant -- Free Persons, Empty Selves / Karin Meyers -- Free Will and Volunteerism in Jainism / Christopher Key Chapple -- Paninian Grammarians on Agency and Independence / George Cardona -- Nyaya's Self as Agent and Knower / Matthew R. Dasti -- Freedom Because of Duty / Elisa Freschi -- Just Another Word for Nothing Left to Lose / Jay L. Garfield -- Self, Causation, and Agency in the Advaita of Sankara / Sthaneshwar Timalsina -- The Linguistics and Cosmology of Agency in Nondual Kashmiri Saiva Thought -- Free Will, Agency, and Selfhood in Ramanuja / Martin Ganeri -- Dependent Agency and Hierarchical Determinism in the Theology of Madhva / David Buchta -- Agency in the Gaudiya Vaisnava Tradition / Satyanarayana Dasa and Jonathan B. Edelmann
Includes bibliographical references and index
Keywords: Philosophy, Indic; Self (Philosophy) -- India; Free will and determinism -- Religious aspects